2016
DOI: 10.1186/s13063-016-1499-6
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin in Youth: N-of-1 trials in a stimulant-treated ADHD Population (MYNAP): study protocol for a randomized controlled trial

Abstract: BackgroundAttention-deficit/hyperactivity disorder (ADHD) is a common neurological disorder affecting 5 % of children worldwide. A prevalent problem for children with ADHD is initial insomnia. The gold standard treatment to manage ADHD symptoms is stimulant medications, which may exacerbate the severity of existing initial insomnia. Currently, no gold standard treatment option exists for initial insomnia for these children. Melatonin, a hormone and a popular natural health product, is commonly provided to chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The posterior estimates of the individual treatment effects represent weighted averages of the individual’s measurements and the average effect. Ultimately, these individual posterior estimates may be used to inform individuals of their response to treatment in light of how others have responded.”55…”
Section: Section 3c: Methods—data Collection Management and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The posterior estimates of the individual treatment effects represent weighted averages of the individual’s measurements and the average effect. Ultimately, these individual posterior estimates may be used to inform individuals of their response to treatment in light of how others have responded.”55…”
Section: Section 3c: Methods—data Collection Management and Analysismentioning
confidence: 99%
“…“Any significant amendments to the protocol will be submitted to Health Canada, Therapeutic Goods Australia, and to the University of Alberta and University of Queensland ethics committees for approval. Trial registries will also be notified of any major amendments.”55…”
Section: Section 3d: Methods (Monitoring)mentioning
confidence: 99%
See 1 more Smart Citation
“…Coxeter et al reported the effectiveness of valerian versus placebo in 24 patients with chronic insomnia [15]. Punja et al have described a protocol to assess the effectiveness of melatonin in children (ages [6][7][8][9][10][11][12][13][14][15][16][17] taking medications for ADHD [16]. Nikles et al have described a protocol to assess the effectiveness of melatonin in patients with PD [17].…”
Section: Chronic Insomnia: a Testbed For Implementation Of N-of-1 Trialsmentioning
confidence: 99%
“…We are also aware of an ongoing N-of-1 randomized controlled trial to assess the effects of melatonin on sleep in youth with ADHD treated with psychostimulants [11]. Finally, although there have been additional studies, the impact of surgery for ADHD-like symptoms in children with ADHD, we could not retrieve any RCT specifically focusing on this.…”
mentioning
confidence: 99%